Effects of Radiation sterilization Dose on the Molecular Weight and Gelling Properties of Commercial Alginate Samples - Mollah, M. Z. I.; Rahaman, M S.; Faruque, M R I.; Khandaker, M U.; Osman, Hamid; Alamri, Sultan; Al-Assaf, Saphwan (Frontiers in Materials, 2021)
To estimate the molecular weight (Mw) and gelling properties, a total of 26 alginate samples consisting of control (n = 13) and 15 kGy γ-irradiated (n = 13) samples were characterized through viscometric and gel permeation chromatography (GPC-MALLS) methods. Based on the observations, a remarkable decrease in the intrinsic viscosity of all samples of alginates was evident due to the effects of radiation, with a linear relationship between viscosity and concentration in 0.01 M NaCl solution. The correlation among the Mw, percentage mass recovery, radii of gyration (Rz/Rg), and percentage reduction of Mw assessed by GPC was significant. The Mw decreased dramatically (from 3.1 × 105 to 0.49 × 105 mole/g in sample no. 12) by the effect of radiation with momentous relation to the % reduction of the molecular weight. The highest molecular weight reduction (84%), which is the most sensitive to γ-radiation, and the average reduction rate was ≥50%. The mass recovery was 100% obtained from samples no. 1,3,4,5,7,12, and 13, while the rest of the samples’ recovery rate was significantly higher. The reduction rate of mass molecular weight (Mw) is higher than the average molecular weight (Mv), but they showed a sensitivity towards radiation, consequently their performance are different from each other. The stability test was performed as a critical behaviour in the control, recurrently same as in the irradiated samples. Thus, the sterilization dose of 15 kGy for the Mw distribution, and subsequently for the characterization, was significantly effective.